Konsep Corporate Social Responsibility Berbasis Pangadarang Wija To Luwu - Nurdea Sahib; Rismawati Rismawati; Andika Rusli; Hapid Hapid (Jurnal Akademi Akuntansi, 2023)
This study aims to reconstruct the concept of CSR with the values contained in pangadarang so that it can provide a new perspective on the concept of CSR. This aim proposes an interpretive paradigm and ethnographic method to understand and reconstruct the concept of CSR with the local wisdom of Pangadarang. This study uses two methods in ethnography, namely the step-by-step method and the inculturative critical ethnography method. The customary order contains customary rules “Pattuppui ri-Ada'e, Mu pasanrei ri-Syara'e”, an affirmation to always be sami'na wa atho'na against God's commands and always uphold the values of local wisdom in order to be human. who is dignified and always has hablum minannas. Research shows that companies must uphold the values of sipakatau, sigunakannge' and sipakalebbi in establishing social relationships. To protect the surrounding environment, companies must also apply the makkasiwiang culture as a quality control in managing nature. This application can be a social capital that can bring benefits to the company.